Analysis of Bound Carbon Content and Combustion Rate of Banana Peel Waste Biobriquettes - Irving Josafat Alexander; Gloria Sirait; Ramlan Silaban; Timotius Agung Soripada; Sunggu Sirait; Adriel Yakobus Nathaniel (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This study aims to analyze the fixed carbon content and combustion rate of briquettes made from banana peel waste as a renewable energy alternative. The experimental method was used, involving key stages such as material preparation, carbonization process, briquette molding, and testing of fixed carbon content and combustion rate. The results showed that the fixed carbon content of the produced briquettes reached 87%, indicating good combustion quality and high energy storage capacity. Additionally, the combustion rate of the briquettes varied, with Sample A having a combustion rate of 0.017 grams/s and Sample B at 0.014 grams/s. This difference suggests that Sample B has a longer combustion duration. Thus, banana peel briquettes have the potential to be an efficient and environmentally friendly alternative fuel. Further research is needed to optimize the production process and enhance briquette efficiency.